Pengaruh Konflik Peran, Ketidakjelasan Peran Dan Kelebihan Peran Pada Kinerja Auditor Dengan Kecerdasan Emosional Sebagai Variabel Pemoderasi (Studi Empiris pada Kantor Akuntan Publik di Surakarta dan D.I Yogyakarta) - Syafariah, Zulfati Mawaddah; , Dr. Noer Sasongko, S.E., M Si., Akt., CA (2017)
This study aimed to examine the effect of role conflict, role ambiguity, and role overload on the performance of auditors with emotional quotient as moderating variables. Auditor when carrying out field work assignments, doing boundary spanning activity (BSA). Individuals who are at the boundary spanning are potentially experiencing role stress. There are three types of role stress those are role conflict, role ambiguity and role overload. Respondents in this study is the auditors who work for Public Accounting Firms in Surakarta and D.I Yogyakarta. The method of determining the sampel is by using purposive sampling method, while the data processing method used by researcher are the multiple regression analysis and moderate regression analysis. The results shows that the role conflict and role ambiguity do not an effect on the performance of auditors, but role overload have a effect on the performance of auditors. Emotional quotient does not moderate interaction between role conflict and role ambiguity on the performance of auditors, but emotional quotient moderates the interaction between role overload on the performance of auditors.